Dry matter intake, body condition score, beta-hydroxy-butyrate, milk yield, and composition of Holstein and crossbred Holstein x Simmental cows during the transition period - Knob D.A.* (2021)
© 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.We compared the dry matter intake (DMI), body condition score (BCS), body weight (BW), beta-hydroxy-butyrate (BHB), milk yield, and milk composition during the transition period of Holstein and crossbred Holstein x Simmental cows. Thirty cows were used in the study. Each cow entered the study 21 days before their expected calving day (prepartum) and remained in the study until day 21 after calving (postpartum). DMI, and milk yield were recorded daily. Once a week, BW and BCS were recorded and blood was collected to measure the BHB. The SAS software was used for the statistical analysis. Holstein and crossbred Holstein x Simmental cows had similar DMI during the prepartum and postpartum periods with higher intakes after calving. Crossbred Holstein x Simmental cows had a higher BCS than Holstein cows during the prepartum and postpartum periods. BHB does not differ between genetic groups, but between periods–with lower values in the prepartum period. The genetic groups had similar milk yield and composition. Both genetic groups lost BCS after calving, but Holstein cows showed a greater decrease in BCS. The use of a crossbreeding programme with Simmental has no negative effect on the performance during the transition period in Holstein herds.